2011
DOI: 10.3892/etm.2011.373
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of HIF-1α expression and radiation resistance in acute hypoxic conditions

Abstract: Abstract.Recently, it has become clear that acute hypoxia affecting radioresistance exists widely in tumor tissues. Concurrently, hypoxia-inducible factor-1α (HIF-1α) is recognized as an essential transcriptional factor, enabling cells to survive through hypoxia. However, it is unclear as to whether HIF-1α plays a direct role in the radioresistance caused by acute hypoxia. Therefore, in this study, we investigated the in vitro response of the human lung adenocarcinoma cell line, A549, to ionizing radiation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Our data showed that under hypoxic conditions, digoxin reduced the viability of A549 cells in a concentration- and time-dependent manner (Figure 1), indicating the potent effect of digoxin on the suppression of tumor cell growth. Furthermore, our results, which are consistent with those of the previous study, showed that hypoxia slightly reduced A549 cell viability compared with the cells under normoxic conditions (Figure 1) [21]. …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our data showed that under hypoxic conditions, digoxin reduced the viability of A549 cells in a concentration- and time-dependent manner (Figure 1), indicating the potent effect of digoxin on the suppression of tumor cell growth. Furthermore, our results, which are consistent with those of the previous study, showed that hypoxia slightly reduced A549 cell viability compared with the cells under normoxic conditions (Figure 1) [21]. …”
Section: Resultssupporting
confidence: 93%
“…HIF-1α has been considered as a potential therapeutic target of several cancers [8,20]. A number of genes involved in cell proliferation, cell survival, angiogenesis, tumor cell immortalization, stem cell maintenance/de-differentiation, genetic instability, autocrine growth, invasion/metastasis, and treatment failure, are upregulated under hypoxic conditions through the activation of HIF-1 [7,8,21]. …”
Section: Resultsmentioning
confidence: 99%
“…The oxygen concentration was assessed in real time using an oxygen electrode (UOE-04 T, Unique Medical, Tokyo, Japan). The details are reported elsewhere [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some HIF-1 inhibitors have been developed and tested in combination with conventional radiotherapy. The results for this combination-therapy have been controversial, with some studies observing no radiosensitizing effect and other studies observing a suppressed tumor recurrence after treatment (172)(173)(174)(175). Combining particle therapy and HIF-1 inhibitors has not been investigated so far.…”
Section: Hypoxiamentioning
confidence: 99%